HYPOXIA AND REPRODUCTIVE HEALTH: The presence and role of hypoxia in the endometrium. Issue 1 (January 2021) - Martínez-Aguilar, Rocío; Kershaw, Lucy E; Reavey, Jane J; Critchley, Hilary O D; Maybin, Jacqueline A
Abstract : The endometrium is a multicellular tissue that is exquisitely responsive to the ovarian hormones. The local mechanisms of endometrial regulation to ensure optimal function are less well characterised. Transient physiological hypoxia has been proposed as a critical regulator of endometrial function. Herein, we review the literature on hypoxia in the non-pregnant endometrium. We discuss the pros and cons of animal models, human laboratory studies and novel in vivo imaging for the study of endometrial hypoxia. These research tools provide mounting evidence of a transient hypoxic episode in the menstrual endometrium and suggest that endometrial hypoxia may be present at the time of implantation. This local hypoxia may modify the inflammatory environment, influence vascular remodelling and modulate endometrial proliferation to optimise endometrial function. Finally, we review current knowledge of the impact of this hypoxia on endometrial pathologies, with a focus on abnormal uterine bleeding. Throughout the manuscript areas for future research are highlighted with the aim of concentrating research efforts to maximise future benefits for women and society.